Global yield curve dynamics and interactions: A dynamic Nelson-Siegel approach - Francis X. Diebold; Canlin Li; Vivian Z. Yue (Goethe University Frankfurt, Center for Financial Studies (CFS), 2007)
The popular Nelson-Siegel (1987) yield curve is routinely fit to cross sections of intra-country bond yields, and Diebold and Li (2006) have recently proposed a dynamized version. In this paper we extend Diebold-Li to a global context, modeling a potentially large set of country yield curves in a framework that allows for both global and country-specific factors. In an empirical analysis of term structures of government bond yields for the Germany, Japan, the U.K. and the U.S., we find that global yield factors do indeed exist and are economically important, generally explaining significant fractions of country yield curve dynamics, with interesting differences across countries.
urn:nbn:de:hebis:30-57654
Keywords: G1; E4; C5; 330; Term Structure; Interest Rate; Dynamic Factor Model; Global Yield; World Yield; Bond Market; Rentenmarkt; Kapitalertrag; Zinsstruktur; Internationaler Finanzmarkt; Deutschland; Japan; Großbritannien; USA